FEMINIST VISION IN NAYANTARA SAHGAL'S NOVELS (International Journal of Food and Nutritional Sciences, 2021)
Nayantara Sahgal is a socialite who is knowledgeable about current social and political issues. Herunderstanding of feminism is based on the Indian spirit. It challenges age-old sexist ideas. Self-discovery is his mainconcern. Her novels focus on modern Indian women's quest for sexual freedom and individuality. The relationshipbetween men and women is an important theme in Sahgal’s stories.Nayantara Sahgal's tone has become more serious due to dissatisfaction in her married life. The malechauvinism he experienced there and the great injustices towards women in society caused him to loudly protest theexploitation of women. In our sacred writings, women are likened to the Creator and deified.In fact, in our society, women have been subjugated and oppressed since ancient times. Man used it,received comfort, joy and support from it, but at the same time it deprived him of the right to happiness and personaldevelopment. Although submissive not by nature but by training, a woman often becomes defiant when she endureswear and tear for a long time. Remove all obstacles. Nayantara focused on the pain of the ancestors. A man's will ishis right, but there are some patterns that a woman must correct herself first, otherwise she will be crushed andfinished. As a feminist, Nayantara argues that women should recognize themselves as human beings.